2020
DOI: 10.1186/s13643-020-01531-2
|View full text |Cite
|
Sign up to set email alerts
|

Research on simulation in radiography education: a scoping review protocol

Abstract: Background Today, there are fewer opportunities for health care students and staff for skills training through direct patient contact. The World Health Organization therefore recommends learning about patient safety through hands-on experience and simulation. Simulation has the potential to improve skills through training in a controlled environment, and simulation has a positive effect on knowledge and skills, and even patient-related outcomes. Reviews addressing the use of simulation across the different rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Simulation has the potential to improve procedural skills through training in a safe, controlled environment, and simulation has a positive effect on knowledge and skills, and even patient-related outcomes [30] . Radiography being a hands-on profession requires practitioner to gain substantial active participation rather than just theory exposure.…”
Section: Technology-enhanced Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulation has the potential to improve procedural skills through training in a safe, controlled environment, and simulation has a positive effect on knowledge and skills, and even patient-related outcomes [30] . Radiography being a hands-on profession requires practitioner to gain substantial active participation rather than just theory exposure.…”
Section: Technology-enhanced Toolsmentioning
confidence: 99%
“…Radiography being a hands-on profession requires practitioner to gain substantial active participation rather than just theory exposure. Therefore, suggestions on incorporating simulation to training or the use of task trainers in procedural skills acquisition is not unheard of [3] , [30] .…”
Section: Technology-enhanced Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Simulation has the potential to improve skills and skill retention through active training in a controlled environment. 41 Studies have shown that learning through simulation improves knowledge and skills and can improve patient outcomes. [42][43][44][45][46][47][48][49] Simulation enhances perceptions of self-efficacy and critical thinking skills in image evaluation and assessment and can lead to more accurate diagnoses.…”
Section: Hands-on and Simulation Trainingmentioning
confidence: 99%
“…The aforementioned issues were poorly investigated in the context of the allied healthcare program. 8 , 9 Author believes that the study will open the door for the researchers to thoroughly explore these issues and provide solutions…”
Section: Introductionmentioning
confidence: 99%